2023
DOI: 10.1590/ce.v28i0.83871
|View full text |Cite
|
Sign up to set email alerts
|

Classificação De Pacientes E Dimensionamento De Pessoal De Enfermagem Em Unidade De Internação Pediátrica

Abstract: RESUMO Objetivo: descrever a implantação do Sistema de Classificação de Pacientes e o dimensionamento do pessoal de enfermagem em unidade de internação pediátrica. Método: estudo descritivo, transversal e retrospectivo, realizado em um hospital universitário do Centro-Oeste do Brasil. Depois da implantação do Sistema de Classificação de Pacientes pediátricos, compilaram-se dados das classificações do nível de complexidade assistencial (N=4.639) entre pacientes (n=608) internados de janeiro a dezembro de 2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
2
0
4
Order By: Relevance
“…A study carried out in clinical and surgical inpatient beds, of an inpatient unit in a public hospital of the Midwest region, showed that the classification of patients of both admissions was similar to that found in the CO admission profile of this research and that could not be observed in the SO, in which a greater demand of patients in low care dependence was also expected. 21 This study observed a higher percentage of patients who fit into minimum and intermediate care. In minimal care, patients are physically self-sufficient in meeting basic human needs, and those classified as intermediate care are partially dependent on the Nursing team to meet their basic human needs.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…A study carried out in clinical and surgical inpatient beds, of an inpatient unit in a public hospital of the Midwest region, showed that the classification of patients of both admissions was similar to that found in the CO admission profile of this research and that could not be observed in the SO, in which a greater demand of patients in low care dependence was also expected. 21 This study observed a higher percentage of patients who fit into minimum and intermediate care. In minimal care, patients are physically self-sufficient in meeting basic human needs, and those classified as intermediate care are partially dependent on the Nursing team to meet their basic human needs.…”
Section: Discussionmentioning
confidence: 57%
“…The sum of the points for each indicator can be from a minimum of 11 points to a maximum of 44 points. This instrument defines five care categories, according to the complexity of care of patients, as follows: intensive care (score above 34); semi-intensive care (29-34); high dependency care (23-28); intermediate care (18)(19)(20)(21)(22) and minimal care (12)(13)(14)(15)(16)(17). 14 The Fugulin instrument was chosen because, among those available in the literature, it is the one developed to evaluate adult patients hospitalized in Clinical and Surgical Units, 14 in addition to being recommended by COFEN by Resolution 293/2004.…”
Section: Complexity Of Care For Oncologic Patientsmentioning
confidence: 99%
“…Um estudo realizado em leitos de internação clínica e cirúrgica, de uma unidade de internação em um hospital público da região Centro-Oeste, evidenciou que a classificação de pacientes de ambas as internações foi semelhante à encontrada no perfil da internação da OC desta pesquisa e que não pode ser observada na CO, na qual se esperava uma maior demanda também de pacientes em baixa dependência de cuidados. 21 Este estudo observou um maior percentual de pacientes que se enquadram em cuidados mínimos e intermediários. No cuidado mínimo, os pacientes são fisicamente autossuficientes quanto ao atendimento das necessidades humanas básicas, e os classificados como cuidados intermediários dependem parcialmente da equipe de Enfermagem para suprir suas necessidades humanas básicas.…”
Section: Discussionunclassified
“…A soma dos pontos de cada indicador pode ser de, no mínimo, 11 pontos a, no máximo, 44 pontos. Este instrumento define cinco categorias de cuidados, de acordo com a complexidade assistencial dos pacientes, sendo elas: cuidados intensivos (pontuação acima de 34); cuidados semi-intensivos (29-34); cuidados de alta dependência (23-28); cuidados intermediários (18)(19)(20)(21)(22) e cuidados mínimos (12)(13)(14)(15)(16)(17). 14 Optou-se pelo instrumento de Fugulin, pois, dentre os disponíveis na literatura, é o que foi desenvolvido para avaliar pacientes adultos internados em unidades de Clínica Médica e Cirúrgica, 14…”
Section: Complexidade Assistencial De Pacientes Oncológicosunclassified
“…Desse modo, em unidades de internação cirúrgica, a demanda de trabalho voltada à enfermagem assistencial é extensa, visto que abrange uma alta carga de atividades a pacientes que demandam de cuidados mais específicos devido a sua complexidade. Logo, a oportunidade de vivenciar de forma contínua, o cenário do PE, através do SAEP propicia a aquisição de conhecimentos teórico-científicos em meio ao cuidado integralizado em indivíduos em situação de internação hospitalar (MORAES et al, 2021).…”
Section: Introductionunclassified